Quantifying cognition and fatigue to enhance the sensitivity of the EDSS during relapses. (June 2021) - Morrow, Sarah A; Conway, Devon; Fuchs, Tom; Wojcik, Curtis; Unverdi, Mahmut; Yasin, Faizan; Pol, Jeta; Eckert, Sveltlana; Hojnacki, David H; Dwyer, Michael; Zivadinov, Robert; Weinstock-Guttman, Bianca; et al.
Background: Cognition is affected by relapses in persons with multiple sclerosis (PwMS), yet the Expanded Disability Status Scale (EDSS) does not readily detect cognitive changes. Objective: The objective of this study is to improve the detection of cognitive decline during relapses, by incorporating the Symbol Digit Modalities Test (SDMT) into the cerebral Functional System Score (CFSS) of the EDSS. Methods: This prospective study recruited PwMS from three dedicated MS centers. All subjects had EDSS, SDMT, and Fatigue Severity Scale (FSS) administered. Subjects experiencing a relapse were assigned to the relapse group (RG). Matched controls from the larger cohort were assigned to the stable group (SG). RG and SG subjects underwent the same evaluation at relapse and 3 months later. Our main outcomes were a modified CFSS (m-CFSS) and modified EDSS (m-EDSS), incorporating SDMT and FSS, accounting for cognitive performance and fatigue rating, during relapse. Results: The full cohort included 592 subjects; 80 qualified for RG and 72 were matched to the SG. The m-CFSS was significantly higher than CFSS at baseline (median = 2 vs. median = 0, p < 0.001) and relapse (median = 2 vs. median = 1, p < 0.001). The m-EDSS was higher than EDSS (median 3.0 vs. 2.5, p = 0.02) at relapse, where 35 RG subjects (43.8%) had higher m-EDSS than EDSS at relapse. Conclusion: This study demonstrates that incorporating the SDMT and FSS improves the accuracy of the EDSS, by accounting for cognitive changes, during relapse activity.